The effect of the number of syn-gas purification nozzles of the water scrubber method on the characteristics of gasification combustion results - Hanggara, Fuad Dwi; Yuliansyah, Fisal; Irawan, Dwi (Politeknik Negeri Lhokseumawe, 2024)
The product of the gasification process contains several impurities, including tar, ash, CO2, and other contaminants. To achieve efficient syngas results, the syngas must undergo a filtration or purification process, which can increase its energy density. The purpose of this study was to determine the effect of the number of purification nozzles on the characteristics of the resulting flame, the duration of the flame produced during the gasification process, and the rate of heat absorption in the water generated from the syngas purification process. The water scrubber method employed in the syngas purification process utilizes an updraft gasification reactor. The biomass used in this study is rubber wood, with a venturi nozzle size of 0.15 mm and a pressure of 0.12 Pa. The tests varied the number of purification nozzles to 2, 3, and 4. The use of 4 nozzles had a significant effect on the combustion characteristics, resulting in a blue flame with a duration of 33 minutes. The configuration with 3 nozzles produced a flame that exhibited a mixture of blue and orange colors, with the blue flame being more dominant, lasting 38.2 minutes. In contrast, the configuration with 2 nozzles resulted in a bluish-red flame, predominantly red in color, with a duration of 45 minutes. The heat absorption rates in the water produced for the configurations with 2, 3, and 4 nozzles were measured at 539 J/s, 449.1 J/s, and 414.62 J/s, respectively.